Role of native Trifolium isthmocarpum populations in saline soils in Morocco - Bennani K.; Bendaou N.; Al Faiz C. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
The potential of previously unexploited crop legume species need to be investigated where environmental and biological stresses constrain the use of more conventional forage crops or where these species are better suited to the needs of sustainable agriculture. The present study have recorded Trifolium isthmocarpum Brot., in many different habitats ranging from healthy agricultural lands to abandoned saline areas. The plants maintained nitrogenase activities average 2.04 μmol C2H4 plant-1 h-1 in different habitats. Shoot systems of plants collected from salt-affected soils exhibited higher concentrations of Na+ and Cl- than those collected from healthy soils, whereas relative water content was reduced by only 8%. This study suggests recommending the cultivation of T. isthmocarpum in moderately salt-affected soils, which are widespread and pose a problem for the farmers of Morocco.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)